Evaluation of intra-individual test-re-test variability of uroflowmetry in healthy women and women suffering from stress, urge, and mixed urinary incontinence - Lunacek, Libor; Gärtner, Marcel; Krhut, Jan; Mika, David; Sykora, Radek; Zvara, Peter (International urogynecology journal, 2018)
INTRODUCTION AND HYPOTHESIS: The objective was to evaluate the intra-individual variability of uroflowmetry (UFM) in healthy control subjects and women suffering from stress, urge, and mixed urinary incontinence. METHODS: A total of 35 healthy controls (group A) and 105 women suffering from urinary incontinence were enrolled in the study. Thirty-five women suffered from stress urinary incontinence (group B), 35 women suffered from mixed urinary incontinence (group C), and 35 women with overactive bladder both dry and wet (group D). All participants were asked to perform UFM measurement three times. The following parameters were analyzed: voided volume (VV), peak flow (Qmax), average flow (Qave), volume-corrected peak flow cQmax (cQmax = Qmax/2√ VV), volume-corrected average flow (cQave = Qave/2√ VV), and postvoid residual volume (PVR). Statistical analysis was performed using the analysis of variance on repeated measurements. Relative error was calculated using variation coefficients reported as a percentage of the average. All descriptive characteristics were reported as means ± standard deviation (SD). p values ≤0.05 were considered statistically significant. RESULTS: No statistically significant intra-individual difference in any of the recorded parameters was identified among the three UFM recordings in groups A, C, and D. The intra-individual variability of the following parameters reached statistical significance in patients suffering from stress urinary incontinence (group B): Qmax (p = 0.0016), Qave (p = 0.0005), and cQave (p = 0.0389). A significant difference was only observed in comparison between the first and second consecutive recordings. CONCLUSIONS: This study provides evidence supporting the high yield and good intra-individual reproducibility of UFM.
Keywords: dospělí; urgentní inkontinence; studie případů a kontrol; Humans; lidé středního věku; Urinary Bladder, Overactive; Middle Aged; reprodukovatelnost výsledků; hyperaktivní močový měchýř; stresová inkontinence moči; Adult; urodynamika; Urinary Incontinence, Stress; Rheology; ženské pohlaví; reologie; lidé; Case-Control Studies; Urodynamics; Reproducibility of Results; Urinary Incontinence, Urge; Female